Disposable Workers: Today's Reserve Army of Labor. - Magdoff, Fred; Magdoff, Harry (Monthly Review: An Independent Socialist Magazine, 2004)
Part of a special issue on the stagnation of employment. The current U.S.-led drive to dismantle international barriers to capital, commonly referred to as “globalization,” is nothing more than the aggressive quest for new, profitable investment opportunities overseas, and it is resulting in decreased job security and social benefits for workers. Capitalism's overall objective is enhanced profitability through greater flexibility in all areas—to hire and fire workers, to secure low-cost labor, to invest and market abroad, to repatriate profits, to gain access to necessary raw materials, and to diminish worker and citizen benefits. The result is a reserve pool of workers that helps to keep costs down, thereby allowing the market system to function profitably, and acting as a perpetual and effective weapon against the workers themselves.